Analysis of Pasar Rakyat Micro Enterprises using Business Intelligent and Data Mining in Jakarta During the Covid-19 Pandemic - Hendra Achmadi (Fakultas Ekonomi Dan Bisnis Universitas Pelita Harapan, 2022)
This study aims to determine the segmentation of the seller at Pasar Jatinegara , and from the data the micro entrepreneur at Pasar Jatinegara mostly is fashion garmen and also home appliances and the rest is a food and bererage, and sales total for a month 55% is below five hundreds rupiahs and 39 % is from range five hundreds until one million a day, and its conclude the Micro Entrepreneurship and most of the seler from the interview has been there for more than 10 years, so these seller is a lower income trap, because they cannot increase skill to increase the revenue or income. As we thought that Indonesia has Go-pay and OVO and Dana, but the reality the seller haven’t have account bank, and never have loan at Bank and do not have a social media, and mostly communicate with sms and most of the seller 32 % is woman dan 68 % is man by using The Business Intelligent. In order to be clear about the segmentation among these seller, then Data mining with machine learning can do that and by using the machine learning with clustering method on the respondent's profile using k-means, in within cluster sum of squares by cluster is 76 %, and it can be seen that the respondent's profile which will increase the intention to use mobile payment is that the total sales are at most under 500 thousand, then the most education in clusters 1 and 3 is at the level of SMA is about 63 percent and the rest are elementary school graduates, and the network that is most widely used is Indosat and the number of suppliers is 1-3 and the number of customers is between 2-10 customers and the last gender is mostly male.